Safety of Oral P2Y12 Inhibitors in Interventional Neuroradiology: Current Status and Perspectives - Camargo, L.M.; Lima, P.C.T.M.; Janot, K.; Maldonado, I.L. (American Journal of Neuroradiology, 2021)
SUMMARY: In the field of interventional neuroradiology, antiplatelet agents are commonly used to prepare patients before the implantation of permanent endovascular materials. Among the available drugs, clopidogrel is the most frequently used one, but resistance phenomena are considered to be relatively common. Prasugrel and ticagrelor were recently added to the pharmacologic arsenal, but the safety of these agents in patients undergoing neurointerventional procedures is still a subject of discussion. The cumulative experience with both drugs is less extensive than that with clopidogrel, and the experience with patients in the neurology field is less extensive than in the cardiology domain. In the present article, we provide a narrative review of studies that investigated safety issues of oral P2Y12 inhibitors in interventional neuroradiology and discuss potential routes for future research.CYPcytochrome P450